IEK-3 Report 2011: Climate-Relevant Energy Research - Emonts, B. (Forschungszentrum Jülich GmbH Zentralbibliothek, Verlag, 2012)
The period under review here – 2009 and 2010 – is characterized by a far-reaching and radical transition to new research fields and structures. This process culminated in October 2010 with the official amalgamation of the Jülich research fields of energy and climate, and the formation of the new and dynamic Institute of Energy and Climate Research. This move united the six institutes focusing on energy and two on climate with the systems analysis with the technology evaluation project group. It aimed to focus activities in specific fields of work, identify common topics for in-depth cooperation, and to generate joint R&D results as solutions to the challenges of the future. The advantages of this concept were demonstrated in 2009 in the form of a PhD thesis jointly supervised by the two research areas on the topic of hydrogen emissions and their impacts on Arctic ozone depletion, which analyzed the risks of a global hydrogen economy. It was then decided that cooperation should be consolidated in these fields. This synergy between energy and climate research at Jülich is globally unique, and is only reflected in part in existing centers for energy and environmental research. In this context, solutions to the growing problem of climate change are also being intensively sought. One possible solution involves the large-scale integration of renewable energy sources into the electricity market and the introduction of electric mobility in the transportation sector. However, considerable research and development efforts are required to provide the vital energy storage technologies of the next generation. These are the challenges that the Helmholtz centers address using their pertinent expertise. Within the framework of the energy storage and hydrogen initiatives, they receive additional funding from the Helmholtz Association (HGF) to implement sufficient R&D measures to help industry provide the key technologies currently lacking for a sustainable energy supply. The formal project conception and proposal for the ...